A Methodology for Understanding and Analyzing Gendered Transformations in Development Planning (G-STARPLAN): A tool in the CGIAR Gender Transformative Research Methodologies (GTRM) toolkit - Osei Amponsah, Charity; Bailey, Arwen; Ewell, Hanna Louise Deborah; Begum, Khadija; Enokenwa Baa, Ojongetakah; Tavenner, Kathleen Anne (2025)
Tool 7 in the Gender Transformative Research Methodologies Toolkit. G-STARPLAN facilitates the integration of gendered transformation analysis into development planning processes. By providing a structured framework and set of guidelines, this toolkit enables researchers to provide insights on context-specific societal dynamics and transformations arising from development interventions and other societal processes, to policymakers, development practitioners, and other stakeholders for evidence-based action. Focus on community and macro level.